Structural and physicochemical effects on the starch quality of the high-quality wheat genotype caused by delayed sowing - Huang, Xiaomei; Zhou, Xin; Liu, Xueqing; Zhong, Wen; Wang, Xinyu; Ju, Zhengchun; Yin, Yan; Xin, Qingguo; Liu, Ning; Liu, Ximei; Jin, Yuli; Wang, Guie; et al. (Frontiers in Nutrition, 2024)
Background: Bread wheat is one of the most important food crops associated with ensuring food security and human nutritional health. The starch quality is an important index of the high-quality wheat. It is affected by a complex series of factors, among which, suitable sowing time is a key factor.To analyze the integrative effects of sowing time on the starch quality of high-quality wheat, in the present study, we selected a high-quality bread wheat cultivar Jinan 17 and investigated the effect of different sowing times on the starch properties and the related genes through analyzing X-ray diffraction patterns, apparent amylose content, thermal properties, pasting properties, in vitro starch digestibility and qRT-PCR. Meanwhile, we also investigated the agronomic and yield performance that may be associated with the starch properties.Results: Delayed sowing had little effect on starch crystalline morphology, but there was a tendency to reduce the formation of crystals within wheat starch granules: 1) delayed sowing for 15 days altered the thermal properties of starch, including onset, peak and termination temperatures and enthalpy changes; 2) delayed sowing for 30 days changed the thermal characteristics of starch relatively insignificant; 3) significant differences in pasting characteristics occurred: peak viscosity and hold-through viscosity increased, while final viscosity, breakdown viscosity and setback viscosity tended to increase and then decrease, suggesting that delayed sowing caused changes in the surface of the starch granules resulting in a decrease in digestibility. Analysis of related genes showed that several key enzymes in starch biosynthesis were significantly affected by delayed sowing, leading to a reduction in apparent straight-chain starch content. In addition to starch properties, thousand kernel weight also increased under delayed sowing conditions compared with normal sowing.The impact of delayed sowing on starch quality is multifaceted and complex, from the fine structure, and functional properties of the starch to the regulation of key gene expression. Our study holds significant practical value for optimizing wheat planting management and maximizing the potential in both quality and yield.